2003
DOI: 10.1590/s0004-282x2003000100015
|View full text |Cite
|
Sign up to set email alerts
|

O uso da estimulação magnética transcraniana de baixa frequência no tratamento da depressão no Hospital Universitário de Brasília: achados preliminares

Abstract: RESUMO -O presente estudo relata o uso da estimulação magnética transcraniana de baixa frequência sobre o córtex pré-frontal direito em três pacientes com diagnóstico de episódio depressivo maior, de acordo com o DSM -IV. Houve melhora significativa em dois pacientes, com diminuição de mais de 50% na pontuação da escala de Hamilton -17 itens. São feitas considerações acerca de possíveis indicações e limitações do seu uso clínico, bem como sugestões ao protocolo de uso desta técnica. Também são discutidos fator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…Since its introduction in 1985 1 , transcranial magnetic stimulation (TMS) has been used as a neurophysiological research tool [2][3][4][5] and more recently, following studies that showed a significant effect of repetitive transcranial magnetic stimulation (rTMS) upon cortical excitability [6][7][8] it has also been considered for the treatment of pathological conditions in which brain excitability is probably abnormal, such as in writer's cramp 9 and depression 10 . Modulation of cortical excitability by TMS in epilepsy was first attempted as a means of causing a silent epileptic focus to become active; this would be useful in the pre-operative evaluation of epilepsy surgery patients.…”
mentioning
confidence: 99%
“…Since its introduction in 1985 1 , transcranial magnetic stimulation (TMS) has been used as a neurophysiological research tool [2][3][4][5] and more recently, following studies that showed a significant effect of repetitive transcranial magnetic stimulation (rTMS) upon cortical excitability [6][7][8] it has also been considered for the treatment of pathological conditions in which brain excitability is probably abnormal, such as in writer's cramp 9 and depression 10 . Modulation of cortical excitability by TMS in epilepsy was first attempted as a means of causing a silent epileptic focus to become active; this would be useful in the pre-operative evaluation of epilepsy surgery patients.…”
mentioning
confidence: 99%
“…To the Editor -I throughly enjoyed the recent paper by Dr. Antonio Aversa do Souto et al 1 , regarding a ventral extradural angiolipoma at the O Potencial Evocado Motor tem contribuído na investigação de várias doenças neurológicas como acidente vascular cerebral, esclerose múltipla, esclerose lateral amiotrófica, doença de Parkinson, mielopatias, ataxias e paraparesia espástica de etiologias diversas. Salienta-se, também, a sua importân-cia na decisão cirúrgica em pacientes com envolvimento medular e o seu valor no acompanhamento e resultado destas intervenções.…”
Section: Lumbosacral Angiolipomaunclassified